1999
DOI: 10.1038/70932
|View full text |Cite
|
Sign up to set email alerts
|

B7-H1, a third member of the B7 family, co-stimulates T-cell proliferation and interleukin-10 secretion

Abstract: The B7 family members B7-1 and B7-2 interact with CD28 and constitute an essential T-cell co-stimulatory pathway in the initiation of antigen-specific humoral and cell-mediated immune response. Here, we describe a third member of the B7 family, called B7-H1 that does not bind CD28, cytotoxic T-lymphocyte A4 or ICOS (inducible co-stimulator). Ligation of B7-H1 co-stimulated T-cell responses to polyclonal stimuli and allogeneic antigens, and preferentially stimulated the production of interleukin-10. Interleukin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

34
1,667
4
16

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 2,231 publications
(1,761 citation statements)
references
References 23 publications
34
1,667
4
16
Order By: Relevance
“…Similarly, injection of mAb to PD-1 [13] or PD-L1 [14] accelerated allograft rejection in immunosup-pressed recipients. However, although most studies indicate that the PD-1/PD-L1 pathway negatively regulates T cell activation and proliferation, there is evidence for a positive costimulatory effect of PD-L1 on TCR activation of naive murine T cells [3,15]. Here, we report data showing that both PD-1 and PD-L1 are essential for the induction and maintenance of allograft tolerance.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Similarly, injection of mAb to PD-1 [13] or PD-L1 [14] accelerated allograft rejection in immunosup-pressed recipients. However, although most studies indicate that the PD-1/PD-L1 pathway negatively regulates T cell activation and proliferation, there is evidence for a positive costimulatory effect of PD-L1 on TCR activation of naive murine T cells [3,15]. Here, we report data showing that both PD-1 and PD-L1 are essential for the induction and maintenance of allograft tolerance.…”
Section: Introductionmentioning
confidence: 75%
“…PD-1 has two ligands, PD-L1 (also known as B7-H1 or CD274), constitutively expressed by many tissues and upregulated on activation [3], and PD-L2 (also known as B7-DC or CD273), expressed primarily by activated DC and macrophages [4]. Upon ligation by either molecule, PD-1 recruits the SHP-1 and SHP-2 phosphatases to its ITSM, leading to dephosphorylation of effector molecules downstream of the TCR and the BCR, such as Syk and phosphoinositide 3-kinase (PI3K), as well as decreasing CD28-mediated activation of PI3K [5].…”
Section: Introductionmentioning
confidence: 99%
“…9,10 PD-L1 is expressed constitutively on both hematopoietic cells (resting T cells, B cells, dendritic cell, macrophages, and regulatory T cells) and nonhematopoietic cells (parenchymal and endothelial cells) and is up-regulated to higher levels by inflammatory stimuli. [11][12][13][14] Peripheral tissue-specific PD-L1 expression indicates that it may have a key role in regulating or terminating immune responses in inflamed tissues. Previous studies from our laboratory and other groups have shown PD-L1 to play a critical function in peripheral immune tolerance as a negative regulator of T-cell responses.…”
mentioning
confidence: 99%
“…PD-1 ligand 1 (PD-L1) and PD-1 ligand 2 (PD-L2), members of the B7 superfamily, are ligands for PD-1 [16][17][18][19]. Mouse (m) PD-L1 and PD-L2 share 38% amino acid identity and have extracellular Ig-like domains [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is also evidence indicating that both PD-L1 and PD-L2 can costimulate T cell responses; i.e. in the presence of suboptimal TCR signals, PD-L1 or PD-L2 can stimulate increased proliferation and production of cytokines in vitro [16,19,20].…”
Section: Introductionmentioning
confidence: 99%